Therapeutic Use of the Antimicrobial Peptide PNR20 to Resolve Disseminated Candidiasis in a Murine Model (2023)
Invasive fungal infections (IFIs) caused by Candida species are an emerging threat globally, given that patients at-risk and antifungal resistance are increasing. Antimicrobial peptides (AMPs) have shown good therapeutic capacity against different multidrug-resistant (MDR) microorganisms. This study evaluated the activity of the synthetic peptide, PNR20, against Candida albicans ATCC 10231 and a MDR Colombian clinical isolate of Candida auris. Perturbation of yeast cell surface was evaluated using scanning electron microscopy. Cell viability of Vero cells was determined to assess peptide toxicity. Additionally, survival, fungal burden, and histopathology of BALB/c mice infected intravenously with each Candida species and treated with PNR20 were analyzed. Morphological alterations were identified in both species, demonstrating the antifungal effect of PNR20. In vitro, Vero cells’ viability was not affected by PNR20. All mice infected with either C. albicans or C. aurisand treated with PNR20 survived and had a significant reduction in the fungal burden in the kidney compared to the control group. The histopathological analysis in mice infected and treated with PNR20 showed more preserved tissues, without the presence of yeast, compared to the control groups. This work shows that the utilization of PNR20 is a promising therapeutic alternative against disseminated candidiasis.